2013
DOI: 10.1080/19338244.2012.732124
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Workplace Violence and Its Effect on Quality of Life Among Medical Professionals In China

Abstract: The present study was conducted to investigate workplace violence and to examine how it is associated with quality of life (QOL) among medical professionals in China. A total of 2,464 medical professionals were selected from Fujian Province and Henan Province by using stratified cluster-sampling method. A Chinese version of the workplace violence scale was used to measure the incidence of workplace violence. The Short Form-36 Health Survey was employed to assess their QOL. Approximately 50% of the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 22 publications
10
49
0
1
Order By: Relevance
“…Over the past few years, China has witnessed a surge in violence against medical professionals. Due to the possible violence which might come at any time and bring danger to their life, physicians have to afford excessive occupational stress, which absolutely will affect their psychological and physical health and then decrease their job performance (26)(27)(28). The current study also found that long duration of nonstop work and poor sleep quality were closely associated with psychological health, which was consistent with the conclusion arrived by previous studies (29)(30)(31).…”
Section: Discussionsupporting
confidence: 91%
“…Over the past few years, China has witnessed a surge in violence against medical professionals. Due to the possible violence which might come at any time and bring danger to their life, physicians have to afford excessive occupational stress, which absolutely will affect their psychological and physical health and then decrease their job performance (26)(27)(28). The current study also found that long duration of nonstop work and poor sleep quality were closely associated with psychological health, which was consistent with the conclusion arrived by previous studies (29)(30)(31).…”
Section: Discussionsupporting
confidence: 91%
“…Emotional exhaustion causes various negative outcomes in the workplace, specifically in terms of organizational performance and commitment (Ashill, Rod, Thirkell, & Carruthers, ; Babakus, Cravens, Johnston, & Moncrief, ; Cropanzano, Rupp, & Byrne, ; Rutherford, Boles, Hamwi, Madupalli, & Rutherford, ; S. Wu et al., ), employee job satisfaction (Babakus et al., ; Lee & Ashforth, ; Rutherford et al., ), and rate of turnover intentions (Boles et al., ; Rutherford et al., ; Singh, Goolsby, & Rhoads, ).…”
Section: Research Background and Hypothesesmentioning
confidence: 99%
“…Robust empirical studies showed that Chinese healthcare workers are exposed to considerable medical violence [12,13,14], and the occupational exposure for healthcare workers in China was worse than that of their global colleagues [15]. This might cause more mental illness and post-traumatic stress disorder (PTSD) [12,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…This might cause more mental illness and post-traumatic stress disorder (PTSD) [12,14,16]. But at the same time, Health China 2030 Plan calls for continuing enhancement of quality of health care [17].…”
Section: Introductionmentioning
confidence: 99%